2008
DOI: 10.1080/15017410701758005
|View full text |Cite
|
Sign up to set email alerts
|

Love in Cyberspace: Swedish Young People with Intellectual Disabilities and the Internet1

Abstract: The Internet has become an increasingly common way for people to contact each other, to flirt, fall in love and start relationships. How does this development influence today's young people with intellectual disabilities? The article presents a picture of the Internet experiences of some young adults with intellectual disabilities and discusses how others view this usage. It is based on a qualitative study in Sweden where 10 young people with intellectual disabilities and 12 staff members were interviewed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(161 citation statements)
references
References 4 publications
5
139
0
17
Order By: Relevance
“…Adults who were interviewed, in the few studies published, like social networking sites (SNS) particularly for keeping contact with parents and friends, making new friends, and giving and receiving support (Holmes & O'Loughlin, 2012;Löfgren-Mårtenson, 2008;Shpigelman & Gill, 2014). The majority of participants from Shpigelman and Gill's (2014) study also reported finding it easier to make new friends by Internet and being more comfortable communicating online than face to face.…”
Section: Internet Use By Adults With Idmentioning
confidence: 99%
See 3 more Smart Citations
“…Adults who were interviewed, in the few studies published, like social networking sites (SNS) particularly for keeping contact with parents and friends, making new friends, and giving and receiving support (Holmes & O'Loughlin, 2012;Löfgren-Mårtenson, 2008;Shpigelman & Gill, 2014). The majority of participants from Shpigelman and Gill's (2014) study also reported finding it easier to make new friends by Internet and being more comfortable communicating online than face to face.…”
Section: Internet Use By Adults With Idmentioning
confidence: 99%
“…Furthermore, adults with ID say that the Internet provides them with a (cyber)space where they can escape their parents' or caseworkers' control and be more self-determined. On the Web, they are freer to "go" where they want and make friends with whom they want, unseen by their guardians and caregivers (Löfgren-Mårtenson, 2008). They can describe their activities and express their feelings in blogs or other social media (McClimens & Gordon, 2009;Shpigelman & Gill, 2014).…”
Section: Internet Use By Adults With Idmentioning
confidence: 99%
See 2 more Smart Citations
“…This is further emphasised when we look at the responses to risk that people with learning disabilities themselves make, compared to their supporters. For example, Lofgren-Martenson (2008) interviewed 10 young people with intellectual disabilities and 12 staff members about their use of the Internet. The results revealed marked differences in risk perceptions.…”
Section: Applying a Positive Risk Taking Framework To Analysis Ofthe mentioning
confidence: 99%